Pedagogies of Respectability: Race, Media, and Black Womanhood in the Early 20th Century. Issue 2 (1st October 2016) - Rhodes, Jane
Abstract : In the early 20th century, a period in which African Americans migrated north from the Jim Crow south in unprecedented numbers, the politics of respectability were a matter of concern for social reformers. Numerous scholars have traced the ways the Great Migration exacerbated class and cultural differences among northern blacks, and the role the black elites played in inculcating respectable behavior. Studies have interrogated the gendered nature of theories of racial uplift and the expectations placed on black women's shoulders. This article examines the role of the black press and black cinema as critical sites for instructing black women, especially those in the working class, on deportment, sexuality, and moral values.